Nie-Marksowski materializm historyczny: założenia i aplikacje - Ciesielski, Mieszko (Studia Europaea Gnesnensia, 2024)
Recenzja: K. Brzechczyn (red.), Non-Marxian Historical Materialism: Reconstructions and Comparison Poznań Studies in the Philosophy of the Sciences and the Humanities, 120, Brill, Leiden-Boston 2022, ss. XVII, 298.